Demographic Policy Construction: Inapt use of Growth Rates Illustrated - ZUBAIR, Hasan (Theoretical and Practical Research in Economic Fields, 2021)
The use of ratios, rates, and percentages is prone to manipulation in demographic policy formulation. That the political and economic benefits get distributed pro rata among various communities, fuels the temptation. Democracies are ruled by the majority community; the temptation thus leads to policies adverse to minorities on false reasoning in self-interest. This brief paper illustrates such a misuse of growth rates in a community coined for the purpose.